Introduction: understanding conflict and processes of state formation, reconfiguration and disintegration in the Horn of Africa - Dias, Alexandra Magnólia (2013)
Since the end of the colonial period, the Horn of Africa (Eritrea, Ethiopia, Djibouti, Somalia, Sudan and South Sudan) has been affected by a large number of inter-state and civil wars (Woodward, 1996). Uganda is part of the region’s security dynamics and a member of its organization, the Intergovernmental Authority on Development.